The battle of the crater : a novel of the Civil War - Gingrich, Newt.; Forstchen, William R.; Hanser, Albert S. (New York : Thomas Dunne Books, 2011)
A tale inspired by the crushing 1864 Union defeat at the Battle of the Crater follows the investigation of reporter and Lincoln confidante James O'Reilly, who retraces the tragedy and how a promising campaign went wrong.
edited hb 2015-06-16
Keywords: Petersburg Crater, Battle of, Va., 1864 -- Fiction; Historical fiction; War stories